Archaeoparasitological Strategy Based on the Microscopic Examinations of Prehistoric Samples and the Recent Report on the Difference in the Prevalence of Soil Transmitted Helminthic Infections in the Indian Subcontinent. (10th September 2018) - Shin, Dong Hoon; Kim, Yong Jun; Bisht, Ravindra Singh; Dangi, Vivek; Shirvalkar, Prabodh; Jadhav, Nilesh; Oh, Chang Seok; Hong, Jong Ha; Chai, Jong Yil; Seo, Min; Shinde, Vasant
Archaeoparasitology is a study to acquire data concerning the parasite infection of ancient people through the examination of the specimens obtained in the excavation sites. Although this research has achieved many successes worldwide, there has been few noteworthy reports from South Asia countries. In 2011 to 2016, we thus conducted parasite examinations on Indian archaeological specimens (n = 247) collected at excavation sites of Mature Harappan period (4600–3900 BP) and their contemporary rural Chalcolithic sites. To derive effective strategy of archaeoparasitological works in Indian Subcontinent, our data were analyzed together with previous clinical report on the soil transmitted helminth infection in the Indian Subcontinent. We propose that future paleoparasitological studies in India should be conducted more intensely on ancient specimens from the states of Assam, Bihar, Jammu and Kashmir, Tamil Nadu, Andhra Pradesh and West Bengal etc.